2011
DOI: 10.4081/reumatismo.2010.202
|View full text |Cite
|
Sign up to set email alerts
|

Survival and death causes in 251 systemic sclerosis patients from a single Italian center

Abstract: INTRODUZIONEL a sclerosi sistemica (SSc) è una malattia acquisita del tessuto connettivo caratterizzata da una tipica vasculopatia del microcircolo, attivazione del sistema immunitario e fibrosi della cute e degli organi interni (cuore, polmoni, reni, apparato gastrointestinale, muscoli, articolazioni, tendini) (1). L'eziologia della SSc è sconosciuta e, nonostante i recenti progressi nella comprensione dei meccanismi patogenetici che ne sono alla base (2), la prevenzione ed il trattamento delle complicanze d'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
2
8
1
2
Order By: Relevance
“…When we limited the definition of the inception cohort to those recruited within 1 year of disease onset, the SMRs were even higher, at 8.1 (95% CI 4.3–12.0) for the Australian cohort, 9.4 (95% CI 6.1–12.8) for the Canadian cohort, and 3.9 (95% CI 2.4–5.4) for the Spanish cohort. The values for Australian and Canadian 1‐year inception cohorts are much higher than those for the corresponding prevalent cohorts and higher than those reported from some previous studies , and they highlight the phenomenon of survivor bias, which leads to underestimation of the true burden of mortality in prevalent cohorts of subjects with SSc. This bias arises in large part because SSc has a substantial burden of early mortality with many deaths occurring within 5 years of disease onset, particularly in men and in the diffuse disease subtype.…”
Section: Discussioncontrasting
confidence: 62%
“…When we limited the definition of the inception cohort to those recruited within 1 year of disease onset, the SMRs were even higher, at 8.1 (95% CI 4.3–12.0) for the Australian cohort, 9.4 (95% CI 6.1–12.8) for the Canadian cohort, and 3.9 (95% CI 2.4–5.4) for the Spanish cohort. The values for Australian and Canadian 1‐year inception cohorts are much higher than those for the corresponding prevalent cohorts and higher than those reported from some previous studies , and they highlight the phenomenon of survivor bias, which leads to underestimation of the true burden of mortality in prevalent cohorts of subjects with SSc. This bias arises in large part because SSc has a substantial burden of early mortality with many deaths occurring within 5 years of disease onset, particularly in men and in the diffuse disease subtype.…”
Section: Discussioncontrasting
confidence: 62%
“…There are several studies on predictors of death in patients with SSc, but only a single-centre cohort study found that DUs were associated with a poorer prognosis in terms of survival 14. Noteworthy, our model includes as independent covariates next to HDU the baseline parameters DLCO and proteinuria, demonstrated by Bryan et al 15 to be, next to age, gender and ESR, the most important predictors on survival 16.…”
Section: Discussionmentioning
confidence: 90%
“…The mortality rate can be underestimated due to the failure to capture data on early death in patients with dcSSc, which could result in overestimation of survival in these patients [ 25 ]. Moreover, patients with dcSSc were reported to have worse outcomes [ 16 , 17 , 19 , 20 ] relative to patients with lcSSc, due to their predisposition toward internal organ involvement, specifically lung and renal involvement. Our study confirmed that a higher mRSS, which manifests as more extensive skin involvement, was a risk factor for mortality in patients with SSc, but no significant difference in 1, 3, 5 and 10-year survival rates was seen between disease subtypes.…”
Section: Discussionmentioning
confidence: 99%